Collisional processes between the Qiangtang Block and the Lhasa Block: Insights from structural analysis of the Bangong–Nujiang Suture Zone, central Tibet. (10th January 2019) - Guo, Runhua; Li, Sanzhong; Yu, Shengyao; Dai, Liming; Liu, Yongjiang; Peng, Yinbiao; Zhou, Zaizheng; Wang, Yuhua; Liu, Yiming; Wang, Qian
Abstract : The Bangong–Nujiang Suture Zone (BNSZ) is one of the main suture zones in the Tibetan Plateau and indicates the existence of the Bangong–Nujiang Neo‐Tethys Ocean (BNO). It was formed by the collision between the Qiangtang and Lhasa blocks after the closure of the BNO. However, its evolutionary processes and subduction polarity remain controversial. Research on the BNSZ is of great significance for exploring plate tectonic evolution and ocean–continent connection. The scarcity of the BNSZ structural data is one of the most important reasons for the debate of the BNO tectonic evolution. Based on structural analysis in the field and combined with previous petrology and palaeomagnetic data, this paper has determined that the closure time of the BNO is progressive and scissor‐like, from Middle Jurassic in the east to Early Cretaceous in the middle and late Early Cretaceous to early Late Cretaceous in the west. There was a three‐stage deformation in the BNSZ: (a) N–S‐directed compression induced by the initial collision; (b) WNW–directed transpression related to the stress adjustment; and (c) NE–SW‐directed compression caused by the low‐angle NE‐directed subduction of the Indus–Yarlung Zangbo Ocean. The different structural pattern along the eastern segment of the BNSZ may have resulted from orogenic bending due to the later Himalayan Orocline caused by the India–Eurasia collision in the Cenozoic.